Boron Nitride‐Based Release Agent Coating Stabilizes Li1.3Al0.3Ti1.7(PO4)3/Li Interface with Superior Lean‐Lithium Electrochemical Performance and Thermal Stability. (20th April 2022) - Zhu, Lei; Wang, Youwei; Wu, Yongmin; Feng, Wuliang; Liu, Zhaolin; Tang, Weiping; Wang, Xiaowei; Xia, Yongyao
Abstract: Sodium super ionic conductor (NASICON)‐type Li1.3 Al0.3 Ti1.7 (PO4 )3 (LATP) is one of the most promising solid‐state electrolytes (SSEs) owing to its high Li‐ion conductivity, high stability with air, and low cost. However, LATP is less widely deployed due to its high incompatibility with lithium metal. Herein, a facile and inexpensive spray‐coating approach is proposed to construct a thin 3D organic/inorganic composite layer of a commercial boron nitride‐based release agent (BNRA) onto LATP. Apart from protecting LATP, this interfacial BNRA layer enables Li‐ion migration through BN defects and affords low resistance at BNRA/Li interface due to in situ formation of Li–N. Compared to bare LATP, which fails to support Li stripping–plating process in a lean‐lithium Li/Li symmetric cell (2 µm), BNRA‐LATP runs for ≈1800 h. The assembled lean‐lithium LiFePO4 (LFP)/BNRA‐LATP/Li solid state batteries (SSBs) deliver a specific capacity of 150.9 mA h g –1 at 0.5 C with minor capacity decay after 500 cycles. Besides, the BNRA layer eliminates thermal runaway risks of LATP‐based SSBs by fast in‐plane thermal dispersion. This work demonstrates a facile LATP‐protection strategy regarding Li incompatibility and thermal runway issues, and pinpoints the interfacial formation mechanism, fulfilling the pursuit of high‐performance low‐cost SSEs. Abstract : A thin 3D interfacial layer of commercial boron nitride‐based release agent (BNRA) is constructed onto Li1.3 Al0.3 Ti1.7 (PO4 )3 (LATP), addressing its Li incompatibility and thermal runway issues, which yields superior electrochemical performance with lean‐lithium (2 µm). This study pinpoints the interfacial Li–N formation mechanism and BN‐defects‐induced Li‐ion migration pathway, verified by the series of materials characterization and density functional theory calculations.